A dictionary journey through ‘staycation’ @ Gamification of English, Mathematics & Science (GEMS) 2022 programme / Marni Jamil, Dr. Nur Husna Serip Mohamad and Dr. Nur Ilianis Adnan - Jamil, Marni; Serip Mohamad, Nur Husna; Adnan, Nur Ilianis (Academy of Language Studies, 2023)
The staycation-themed session was blended with gamification and storytelling elements. Ms. Marni, Dr. Nur Husna, and Dr. Nur llianis from ALS led the dictionary skills slot with the assistance of eight UiTM Penang branch students. For the improvement of language skills, it is undeniable that students need to refer to the dictionary in order to develop their vocabulary to exhibit better performance in their higher education and career. It is pivotal for students to receive proper training in dictionary-use in the language classroom to attain linguistic proficiency in their professional academic settings. Therefore, a slot to teach dictionary skills was integrated into the programme. The first activity conducted was reading out loud by Ms. Marni. This activity is very important as we want to help students to establish comprehension of the reading material as reading out loud is known as the foundation for literacy development. Ms Marni, with various tones and facial expressions, read a brief story about a staycation set in the United Kingdom. Throughout the story, Dr. Husna showed the images of words uttered by Ms Marni such as scenic sights, monuments, summer days and others - an approach known as the multisensory technique where students will see the picture while listening to it simultaneously. After the reading session, Dr. Ilianis explained the importance of using dictionaries when encountering difficult words. To further enhance their vocabulary skills, she continued by giving examples of words on the board and taught them to identify the words according to their sequence in the dictionary. The students were actively involved in giving responses. Within a short period of time, it was observed that most of the students were able to identify the sequence of those words while helping them to acquire a broader vocabulary.